TEMA DAN GAYA BAHASA SEBAGAI METODE DAKWAH (Studi tentang Ayat-Ayat Makkiyah dan Madaniyah) - Rahmadini Rahmadini (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2012)
As we all know that the Quran is received by the Prophet Muhammad over a period of 23 years. It was received when the Prophet was in Mecca (we call Makkiyah) and after he left Mecca (we call it Madaniyah). At the time the Quran was revealed in Makkah, which is at the beginning of receiving the relation (to be prophet), the Muslims were still in a minority and the idol worshippers were majority. Making a dialogue with unbelievers, Muhammad must use the appropriate language style and special method. The caracteristics of Makkiyah and Madaniyah language styles and themes are different. It is one of the best methods in preaching to the path of Allah appropriate with the unbeliever's mental, mind, rhought and feeling. In every stage of preaching, Muhammad (p.u.b.h.) had varied themes and models appropriate with their belief and environtmental condition. They all are revealed in how the Quran invited all people to return to Islam.